Sou mais eu entre duas matrizes de superação : configurações narrativas de questões de gênero em relatos autobiográficos femininos de superação - Juliana Soares Gonçalves (2017)
The present work aims to comprehend, based on the concept of mise in intrigue (RICOEUR, 2010), in which way first person’s narratives that compose the magazine Sou Mais Eu lead to a prism of femininity that emerges from two different matrices of overcoming. That is , based on stories that have as motif episodes of overcoming of multiple natures, it’s of our interest to distinguish what can be overcome and what is treated as being impossible to overcome. While the first narrative points out, in its majority, to contexts of subjection of narrating women to crystallizations of gender as the safe way to happiness, the second narrative, which consists in the dimension of the insuperable, relegates gender inequalities to the status of contingency. Therefore, oppressive situations met on a daily basis by women, like episodes of violence both physical and symbolical, submission to unreachable beauty standards, unequal opportunities in the job market, domestic work overload and the obligation to take care of others, are not problems in these narratives, being incorporated as the normalized condition of a certain way of being a woman. Thus, in an attempt to reflect the way these meanings are configured by their narratives, we have elected two constitutive elements of intrigue to carefully observe: the constitution of the self as a character, inserted in the study of gender questions, and the temporal articulation, that shows itself as a recurrent form of contexture of events in time as essential element in the sense of overcoming.